The Influence of Emotional Intelligence, Industrial Work Practices, Soft Skills, and Self-Efficacy on Students Work Readiness - Febriyana, Nora; Indrawati, Henny; Makhdalena, Makhdalena (FKIP-Universitas Riau, 2023)
Vocational High School is one of the institutions that prepare the workforce, Students from Vocational High School should have good work readiness to work immediately. However, based on data from the Central Statistics Agency (BPS), Indonesia has the highest open unemployment rate for SMK graduates compared to other levels of education. This study aims to determine the effect of emotional intelligence, industrial work practices, soft skills, and self-efficacy on students' work readiness. This study uses a descriptive method with a quantitative approach. The research subjects were class XII students majoring in Accounting at SMKN 1 and SMKN 6 Pekanbaru City. The population in this study totalled 233 students and a sample of 147 students. The sampling technique used is Proportional Random Sampling. The data analysis technique uses descriptive analysis and multiple linear regression equations with the help of SPSS. The results showed that work readiness as a variable (Y) was simultaneously influenced by emotional intelligence (X1), industrial work practices (X2), soft skills (X3) and self-efficacy (X4) in Pekanbaru City Vocational High School students.